Constitutional Liberalism and the Brazilian Empire:: A Joint Analysis of the Work of Joao Camilo de Oliveira Torres - Boeira, Marcus Paulo Rycembel (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The article intends to demonstrate the influence that a particular type of political liberalism has had on the institutionalization of the Brazilian Empire, and thus on the work of João Camilo de Oliveira Torres as a whole. Therefore, we must recognize that this author was not a true sense liberal, but a thinker who drew from liberalism certain theoretical nuances which were consistent with a conservative and Catholic social matrix in the principles field of social studies. The camilist vision of liberalism is consistent with the Austrian School as a whole, but it keeps certain differences.